2013
DOI: 10.4314/ahs.v12i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive practices adopted by women attending an urban health centre

Abstract: Background: India was the first country in world to launch -The National Family Welfare Programme in1951 but even today the couple protection rate (CPR) is still not achieved as desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 11 publications
9
41
2
Order By: Relevance
“…[12] A high proportion of unmet need in the present study could be due to the reason that among those who were not practising FP methods 25% cited that their husbands were staying away from home for work. In the present study, unmet need was found to be higher among the Muslims which were similar to other studies, [7,13] but Patel et al study and Indu [14] in their studies reported that unmet need was high among the Hindus. In the present study, 8.3% of the Muslims had cited need of FP method use was not felt, while 2.8% religious taboos was the major hindrance of non-usage.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…[12] A high proportion of unmet need in the present study could be due to the reason that among those who were not practising FP methods 25% cited that their husbands were staying away from home for work. In the present study, unmet need was found to be higher among the Muslims which were similar to other studies, [7,13] but Patel et al study and Indu [14] in their studies reported that unmet need was high among the Hindus. In the present study, 8.3% of the Muslims had cited need of FP method use was not felt, while 2.8% religious taboos was the major hindrance of non-usage.…”
Section: Discussionsupporting
confidence: 81%
“…[5] However, the findings are in concurrence with a study done by Prateek and Saurabh who reported 28.9% [7] had unmet need for spacing and 22.7% had unmet need for limiting in Africa as well as a study done in Western part of India by Patel et al which was 20.50%. [8] Unmet need was much higher in Lucknow as reported by a study done by Pal et al (53.1%), [10] Vohra et al (35%) in Jaipur, [11] and Singh et al in Patiala where unmet need for spacing was 23.5%.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…On the other hand, a much varying prevalence of 51 % among women of reproductive age group was reported by Prateek et al in a study done at Kancheepuram district, Tamil Nadu. However, the participants of the above study were those who attended the OPD of an urban health center [17]. The difference in prevalence of unmet need for family planning between our study and the national data could be possibly due to lack of persistent emphasis on family welfare services in the country.…”
Section: Discussionmentioning
confidence: 87%